Creating a Safe School Environment in the Digital Era: Behavioral Modification Strategies in Preventing Cyberbullying - Nawawi, Erfan (Samsara Institute Publisher, 2025)
Cyberbullying is a form of psychological violence that occurs through digital media and has become increasingly prevalent among students. This study aims to examine behavior modification strategies for preventing cyberbullying. This review employs a literature-based approach, analyzing articles published between 2015 and 2024. The findings indicate that cyberbullying has distinct characteristics compared to conventional bullying, particularly in terms of method, intensity, and psychosocial impact. Factors influencing both perpetrators and victims include individual psychological traits, family dynamics, peer pressure, and the school climate. Effective prevention strategies involve responsive counseling-based interventions, strengthening of digital literacy, and collaboration between schools, families, and communities. This research recommends the development of value- and technology-based guidance programs as a preventive and promotive effort to create a safe and empathetic school environment.